Comparison of Quality of Life in Parents of Premature Infants: A Cross-Sectional Study - Zahra Kashaninia; Farzad Alizadeh; Shima Haghani; Alireza Ghanbari (Journal of Mazandaran University of Medical Sciences)
Background and purpose: According to the World Health Organization (WHO), approximately 15 million preterm infants are born each year, accounting for more than 10% of all births. The hospitalization of premature infants can significantly impact the daily lives of parents and may negatively affect their quality of life. This study aimed to compare the quality of life between fathers and mothers of premature infants referred to health centers in Amol, Iran. Materials and methods: This cross-sectional study was conducted on 79 couples (mothers and fathers) of premature infants who visited health centers in Amol for vaccination, using convenience sampling. Inclusion criteria were singleton birth, absence of congenital anomalies or severe physical illness, and no history of neurological disorders. The exclusion criterion was a birth weight of less than 1500 grams. Data were collected using a demographic information checklist and the World Health Organization Quality of Life Questionnaire (WHOQOL-BREF), which contains 26 questions across four domains. The questionnaire was completed by both mothers and fathers. Descriptive statistics (mean, standard deviation, frequency, and percentage) and analytical statistics (paired t-test and ANOVA) were used for data analysis. Results: The mean (± standard deviation) of the overall quality of life score was 67.56 ± 16.68 for mothers and 67.08 ± 17.23 for fathers. Paired t-test results showed no significant differences in the quality of life between mothers and fathers in most domains (physical health, social relationships, and environment) (P> 0.05); however, in the psychological domain, fathers reported a significantly higher quality of life (P= 0.030). Conclusion: The results indicated that the overall quality of life of mothers and fathers with premature infants was generally similar; however, fathers reported higher scores in the psychological domain. These findings emphasize the importance of addressing the psychological and emotional needs of parents, especially mothers, and developing targeted interventions to improve their quality of life.